Dual regulation by ethanol of the inhibitory effects of ketamine on spinal NMDA-induced pressor responses in rats - Keng, Nien-Tzu (BioMed Central, 2012)
BACKGROUND: Acute exposure of ethanol (alcohol) inhibits NMDA receptor function. Our previous study showed that acute ethanol inhibited the pressor responses induced by NMDA applied intrathecally; however, prolonged ethanol exposure may increase the levels of phosphorylated NMDA receptor subunits leading to changes in ethanol inhibitory potency on NMDA-induced responses. The present study was carried out to examine whether acute ethanol exposure influences the effects of ketamine, a noncompetitive NMDA receptor antagonist, on spinal NMDA-induced pressor responses. METHODS: The blood pressure responses induced by intrathecal injection of NMDA were recorded in urethane-anesthetized rats weighing 250-275 g. The levels of several phosphorylated residues on NMDA receptor GluN1 subunits were determined by western blot analysis. RESULTS: Intravenous injection of ethanol or ketamine inhibited spinal NMDA-induced pressor responses in a dose-dependent and reversible manner. Ketamine inhibition of NMDA-induced responses was synergistically potentiated by ethanol when ethanol was applied just before ketamine. However, ketamine inhibition was significantly reduced when applied at 10 min after ethanol administration. Western blot analysis showed that intravenous ethanol increased the levels of phosphoserine 897 on GluN1 subunits (pGluN1-serine 897), selectively phosphorylated by protein kinase A (PKA), in the lateral horn regions of spinal cord at 10 min after administration. Intrathecal administration of cAMPS-Sp, a PKA activator, at doses elevating the levels of pGluN1-serine 897, significantly blocked ketamine inhibition of spinal NMDA-induced responses. CONCLUSIONS: The results suggest that ethanol may differentially regulate ketamine inhibition of spinal NMDA receptor function depending on ethanol exposure time and the resulting changes in the levels of pGluN1-serine 897.